2020
DOI: 10.1111/aos.14589
|View full text |Cite
|
Sign up to set email alerts
|

Variations and trends in global disease burden of age‐related macular degeneration: 1990‐2017

Abstract: To evaluate the disease burden of age-related macular degeneration (AMD) and to evaluate the risk factors of disability-adjusted life years (DALY) caused by AMD. Methods: Country-specific DALY number, rate and age-standardized rate of AMD were acquired from the Global Burden of Disease Study 2017 database. The Socio-demographic Index (SDI), Human Development Index (HDI), Inequality-adjusted Human Development Index (IA-HDI) and other related data were obtained from published data or shared databases. Regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 23 publications
0
14
1
1
Order By: Relevance
“…SDI is a summary index that can be used to represent the position of a nation on the spectrum of economic development, and different regions in each nation can have significantly different SDI levels (39). A previous study has reported the AMD burden to be higher in low SDI regions (40). However, this study showed that the middle SDI regions demonstrated the highest number of AMD cases and YLDs, and the low SDI region demonstrated the lowest.…”
Section: Discussioncontrasting
confidence: 68%
“…SDI is a summary index that can be used to represent the position of a nation on the spectrum of economic development, and different regions in each nation can have significantly different SDI levels (39). A previous study has reported the AMD burden to be higher in low SDI regions (40). However, this study showed that the middle SDI regions demonstrated the highest number of AMD cases and YLDs, and the low SDI region demonstrated the lowest.…”
Section: Discussioncontrasting
confidence: 68%
“…Kruskal–Wallis H-test was conducted to assess the difference in age-standardized DALY rates across HDI-based categories, followed by Mann–Whitney U-test for post-hoc pairwise comparisons. Stepwise multiple linear regression analysis was conducted to explore the associations between the age-standardized DALY rates of CKD due to hypertension and country-level demographic and socioeconomic factors; commonly used country-level indexes were selected as potential associated factors with CKD attributable to hypertension based on previous published studies ( 23 , 24 , 26 ) and variables at a level of p ≤ 0.2 were selected for inclusion in multiple stepwise regression analysis for further analysis. All statistical analyses were performed by using Stata MP 15.0 (Stata Corp LP, College Station, Texas, USA).…”
Section: Methodsmentioning
confidence: 99%
“…According to published GBD studies on different chronic diseases (22)(23)(24), different country-level demographic and socioeconomic factors were selected from open databases to investigate their correlations with disease burden of CKD due to hypertension. Socio-demographic index (SDI), a composite index reflecting a country's socio-demographic development status, was also extracted from the GHDx (http://ghdx.healthdata.org, accessed 10 Nov 2019).…”
Section: Selection Of Country-level Factorsmentioning
confidence: 99%
“…(5) Inhibition of pyroptosis; (6) Inhibition of carbonyl stress; (7) Inhibition of G 2 /M phase arrest; (8) Inhibition of VEGF activation.…”
Section: Nutritional Treatmentmentioning
confidence: 99%
“…Among those aged 80 years and above, 66% have several signs of AMD [ 4 , 5 ], and 3% of those over 65 years old suffer visual problems caused by AMD [ 6 ]. According to Zou’s study on the global burden of AMD from 1990 to 2017, special groups can significantly suffer from AMD, such as females, the elderly, those from developing countries, and low-educated persons, etc., and from 1990 to 2017, AMD contributed to a doubling of the number of people living a low quality of life [ 7 ]. An even more serious consideration is that the number of global AMD patients has been predicted to rise from 196 million in 2020 to 288 million in 2040 [ 8 ].…”
Section: Introductionmentioning
confidence: 99%